Phytochemical Screening and Anti-hyperglycemic Effect Test of Ethanol Extract of Waru Leaf (Hibiscus tiliaceus) on Glucose-loaded Mice - Vivi Sofia; Tya Novita Firdaus; Muharni Saputri (Universitas Airlangga, 2024)
Background: The treatment of diabetes mellitus relies on synthetic drugs with various side effects. Therefore, it is necessary to explore alternative treatments with herbal therapies, such as Hibiscus tiliaceus leaves. Objectives: The aim of this study was to determine the anti-hyperglycemic effect of an ethanol extract from Hibiscus tiliaceus leaves in glucose-loaded mice. Methods: The initial stage of dried leaf characterization was to ensure the identity, quality, purity, and safety to be used, and then extracted using the maceration method with 70% ethanol solvent. The next step was phytochemical screening to identify secondary metabolite content. The anti-hyperglycemic effect was evaluated using the oral glucose tolerance test (OGTT) on 25 male mice divided into five treatment groups. The negative control group was given Na CMC 0.5% w/v Na CMC, and the positive control group was administered glibenclamide. The ethanol extract of Hibiscus tiliaceus leaves was administered at doses of 200, 400, and 800 mg/kg. Approximately 200 µL of blood was collected and analyzed for glucose levels. The data were statistically analyzed using one-way analysis of variance (ANOVA) with SPSS ver. 25 program. Results: Hibiscus tiliaceus leaves contain alkaloids, flavonoids, saponins, and tannins. The highest decrease in blood glucose levels was observed in the ethanol extract group at a dose of 400 mg/kg BW, with a decrease of 78.52%, followed by a dose of 200 mg/kg BW of 76.63%, a dose group of 800 mg/kg BW of 73.48%, and a positive control group (glibenclamide) of 34.68%, which was significantly different from the negative control group (Na CMC 0.5%) (p < 0.05). Conclusion: The ethanol extract of H. tiliaceus has anti-hyperglycemic effects.